A proposta da Base Nacional Comum Curricular e o debate entre 1988 e 2015 - Ileizi Luciana Fiorelli Silva; Henrique Fernandes Alves Neto; Daniel Vitor Vicente (Ciências Sociais Unisinos)
In this article we analyze the proposals of the Common National Curricular Basis of 2014 and 2015, taking them as public policies and as challenges of Brazilian democracy, set since the enactment of the 1988 Federal Constitution. We then identify the main milestones in the development of national curricular proposals since 1988, focusing on the results after the enactment of the 1996 Law of Guidelines and Bases of National Education – the law that regulates education in Brazil –, as elements to be compared with the two most recent proposals. We find that a methodology for the development of curriculum policies was established that is a consequence of the federalist order in Brazil. This methodology of the Ministry of Education created a channel of communication with the members of the Brazilian federation through the State Departments of Education, the National Board of Municipal Education Officials (UNDIME) and the National Council of Secretaries of Education (CONSED). Besides these agencies and agents, the various organizations of social movements, economic groups, scientific associations and universities were invited and/or volunteered to participate in the processes of the development of curriculum proposals. The analyzed proposals were results of these complex flows of public actions directed at the curriculum of Elementary Education. Thus, they dialogue with the National Curricular Parameters (1998), the National Curricular Guidelines (1998, 2013), the Reference Matrices of the National Examination of Secondary Education and the Elementary Education Assessment System, besides the proposals of States and Counties.